Psychische Belastung des intensivmedizinischen Personals in Deutschland im Verlauf der COVID-19-Pandemie. Evidenz aus der VOICE-Studie - Niecke, Alexander; Henning, Michaela; Hellmich, Martin; Erim, Yesim; Morawa, Eva; Beschoner, Petra; Jerg-Bretzke, Lucia; Geiser, Franziska; Baranowski, Andreas M.; Weidner, Kerstin; Mogwitz, Sabine; Albus, Christian (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2024)
Background: The coronavirus disease 2019 (COVID-19) pandemic posed major challenges to the healthcare system worldwide and led to particular stress among healthcare workers. The aim of this analysis was to investigate the level of global mental stress of direct healthcare workers in Germany during the COVID-19 pandemic. Methods: In this prospective cross-sectional study with four measurement points (T1: 4–5/2020, T2:11/2020–1/2021, 5–7/2021, 2–5/2022), psychological distress symptoms were recorded in an online survey with the Patient Health Questionnaire (PHQ-4) among hospital staff working in direct patient care (N = 5408 datasets). The total dataset was exploratively analyzed according to field of activity, gender, and professional group affiliation. Results: Clinically relevant psychological distress (PHQ-4 ≥ 5) was present in 29.3% (n = 419/1429) of intensive care staff. A comparison of the four cross-sectional surveys showed a significant increase in the rate of clinically relevant mental distress in the first pandemic year (23.2% at T1 vs. 30.6% at T2; p < 0.01), which stabilized at a high level in the second pandemic year (33.6% at T3 and 32.0% at T4). Women did not differ from men in this respect (n = 280/919, 30.4% vs. n = 139/508, 27.4%; p = 0.74). Nursing staff were significantly more often psychologically stressed than physicians (n = 339/1105, 30.7% vs. n = 80/324, 24.7%; p = 0.03). Intensive care staff did not show significantly higher stress than staff working in nonintensive care areas (n = 419/1429, 29.3% vs. n = 1149/3979, 28.7%, p = 0.21). Conclusion: German healthcare workers reported high levels of mental distress during the pandemic, which increased during the course of the pandemic, but no significant difference was found between intensive care and nonintensive care staff in our sample. This may be due to the fact that the pandemic in Germany was comparatively moderate internationally and neither a collapse of the healthcare system in general nor a collapse of intensive care structures in particular took place.
CRIS-Team Scopus Importer:2024-08-16
Keywords: Healthcare workers; Infectious disease; Intensive care medicine; Mental health; PHQ-4